A Bibliometric Analysis of Social Media in Marketing: Mapping Research Trends, Topics, and Keywords from 2019-2024 - Nafisah Arinilhaq; Indah Fatmawati (INJECT (Interdisciplinary Journal of Communication), 2025)
The study investigates scholarly publications to identify dominant themes, keyword occurrences, and citation networks related to social media marketing. This study used VOS Viewer and RStudio. The findings indicate that "social media" is a key focus in academic discourse, emphasizing its importance in audience engagement and business conversion. The study adds theoretical value by mapping current trends and providing insights for future research. Practically, it encourages businesses to adapt to changing social media trends in order to improve their marketing effectiveness. However, because the analysis is limited to bibliometric data, future research should employ case-based or experimental approaches.